Additive manufacturing - Yeong, Wai Yee (Nanyang Technological University, 2022)
Additive manufacturing (AM), or commonly known as 3D printing, gained prominence as part of a suite of technologies that is expected to bring about the Fourth Industrial Revolution, or Industry 4.0. This technology primer aims to showcase the capabilities across the Schools and Research Centres under CoE. While introducing AM, the primer also elucidates the market growth of AM, the exciting new directions undertaken in research development for AM and the current challenges that AM is facing. Applications of AM can be multidisciplinary and span across many fields of study. The research projects featured in this primer are categorised into seven research areas: (1) Aerospace & Defence (2) Biomedical & Food Printing (3) Building & Construction (4) Marine & Offshore (5) AI in Part Design & Manufacturing (6) Novel Materials & 3D Microstructure Engineering (7) Beyond 3D Printing. It is certain that AM will have an important part to play in our journey towards Industry 4.0. There is more to explore with this emerging technology as new players enter the field, bringing new AM methods, materials, and challenges for vastly different applications. Through this primer, we hope to provide a deeper understanding of AM and encourage partnerships between academia and industry to fully unleash the exciting potential of AM and transform the industry through digitalisation of manufacturing.